Turnover in Power as a Restraint on Investing in Influence: Evidence from the Postcommunist Transition - Milanovic, Branko; Hoff, Karla; Horowitz, Shale (2012)
We develop and implement a method for measuring the frequency of changes in power among distinct leaders and ideologically distinct parties that is comparable across political systems. We find that in the postcommunist countries, more frequent changes in power in the early years of transition are associated with better governance in the later years. The results are consistent with the hypothesis that more frequent turnover in power lowers the returns to firms seeking to buy political influence: i.e,. that government turnover serves as a restraint on investing in influence regardless of the ideology of the government.